DISKRIMINASI UPAH BURUH TANI DI KAMPUNG CAMPAKAWANGI KABUPATEN CIANJUR: Wage Discrimination Of Farm Laborers In Campakawangi Village Cianjur Regency - Latya Rachmania Aisha; Wahyuni Retnowulandari (Faculty of Law, Universitas Trisakti, 2025)
Although there are laws that regulate the equal rights of female and male workers, in actuality, the status of women in the workforce falls short of anticipated standards. The phenomenon of wage discrimination against women workers in Indonesia in reality still occurs in various sectors, one of which is in the agricultural sector. Therefore, this research formulates the problem of whether women farm laborers in Campakawangi Village receive the same wage rights as male farm laborers as stipulated in Article 11 paragraph (1) letter (d) of CEDAW. Regulations regarding the rights of women workers are specifically regulated in article 11, especially related to equal pay and equal treatment in paragraph (1) letter (d). The results and conclution of the research found that female farm laborers in Campakawangi Village still get lower wages than male farm laborers, meaning that the right to equal wages is not fulfilled. Women's rights owned by female farm laborers in Campakawangi Village are still not fulfilled due to the strong patriarchal culture, especially the negative labeling of women that has taken root so that women are considered weaker than men, this is the background for the difference in wages for farm laborers. So the role of local government is needed to make regulations and supervision regarding wage standards with a fair system for male and female farm laborers.